The coordination role of the State of Rio Grande do Norte government in response to covid-19: innovation in times of crisis? - Gomes, Sandra; Silva, André Luís Nogueira da; Segatto, Catarina Ianni; Santos, Anderson (Saúde e Sociedade, 2023)
From a case study of the State of Rio Grande do Norte, in Brazil, this article discusses the role of states in coordinating healthcare with its local governments in the context of the new coronavirus pandemic and within a federal polity design. The absence of federal government initiatives in responding to the pandemic in Brazil have been acknowledged by several specialists as an unprecedented event in the Brazilian federation, breaking with a recurrent pattern of national coordination and regulation by different governments since the 1988 democratic Constitution. In this sense, states and municipalities had to adopt their own initiatives to respond to the pandemic. Qualitative research based on the collection of documents (local media, epidemiological reports, and state regulations) and in-depth interviews with state and municipal managers reveals significant changes in the state-municipal relationship throughout the pandemic period in Rio Grande do Norte, a state historically characterized by the lack of state coordination. The pandemic, thus, functioned as an exogenous shock, which induced changes in the pattern of state coordination in healthcare. It is unclear, however, whether these changes are one-off or permanent since the weight of increasing returns – a specification of a path dependency process – seem to work as a mechanism producing inertial dynamics of difficult disruption with the past.